Globalisasi, liberalisasi, dan daya saing sektor pertanian - Soetatwo Hadiwigeno (Economic Journal of Emerging Markets, 1999)
As we know that the globalization and liberalization process have impact in many aspects, economic, and social problems. Indonesia as a developing country will get because of its low competitiveness. The government must develop an appropriate policy to solve this problem.